2002
DOI: 10.1111/j.1151-2916.2002.tb00071.x
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation and Growth of Mullite Whiskers from Lanthanum‐Doped Aluminosilicate Melts

Abstract: Nucleation and growth of mullite whiskers in the La 2 3 _AlA 2 0 3 _SiO 2 system were investigated in the 1500°-1700°C temperature range. A differential thermal analysis (DTA) showed that the mullitization temperature decreases from 1350°C to 1240°C as a result of lanthania doping. In the temperature range of 1250°-1500°C, most of the mullite grains have an AI 2 OJSiO 2 = 1.5 composition throughout the ceramic body; however, from 1400°C upward, the number of anisotropic grains with the AI 2 ,O/SiO 2 = 1.3 comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Regiani et al observed a mullitization temperature of ∼1240 • C in a 3 mol%-La 2 O 3 doped Al 2 O 3 /SiO 2 mixture and claimed that the temperature was very close to the eutectic temperature in the La 2 O 3 -Al 2 O 3 -SiO 2 ternary system [20]. The presence of glass phase, which was responsible for the lowering of the mullite formation temperature, was directly evidenced in the SEM images of the samples' surfaces.…”
Section: Mullitization and Reaction Sequencesmentioning
confidence: 95%
“…Regiani et al observed a mullitization temperature of ∼1240 • C in a 3 mol%-La 2 O 3 doped Al 2 O 3 /SiO 2 mixture and claimed that the temperature was very close to the eutectic temperature in the La 2 O 3 -Al 2 O 3 -SiO 2 ternary system [20]. The presence of glass phase, which was responsible for the lowering of the mullite formation temperature, was directly evidenced in the SEM images of the samples' surfaces.…”
Section: Mullitization and Reaction Sequencesmentioning
confidence: 95%
“…Mullite formation in the presence of lanthanum was recently investigated, [15][16][17] but to the best of our knowledge, crystallization kinetics of lanthanum doped pre-mullite gels has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative way to produce interlocking microstructured mullite ceramics is via in situ processing technique. For a conventional solid-state reaction process, in situ anisotropic grain growth usually takes place at very high temperatures (>1600 • C) [5][6][7][8]. This is because mullite ceramics prepared in this way experienced densification before mullite phase formation.…”
Section: Introductionmentioning
confidence: 98%
“…This suppressed anisotropic growth of mullite grains. In this case, ultra high temperature is essential for the formation of a eutectic liquid to maintain the anisotropic grain growth of mullite in a fully densified sample [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%